HOW ADJUSTMENT COST RELATE WITH STICKINESS COST? - Eltivia, Nurafni; Ekasari, Kurnia; Wahyuni, Hesti; Isrowiyah, Anna (Jurnal Reviu Akuntansi dan Keuangan)
This study aims to analyze stickiness cost and how the adjustment cost affects stickiness cost. Equity intensity is used as a proxy for measuring the adjustment cost. The population of this research is consumer goods company listed on the Indonesia Stock Exchange in 2014-2015, there are 24 companies that became the sample of this study. This research used multiple linear regression to analyze the data. The results showed stickiness cost in consumer goods companies. Further equity intensity is an indicator that can indicate a condition or characteristics of an organization or company that can be used to predict stickiness cost.